2018
DOI: 10.1101/498659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association meta-analysis identifies novel GP2 gene risk variants for pancreatic cancer in the Japanese population

Abstract: The etiology of pancreatic cancer remains largely unknown. Here, we report the results of a meta-analysis of three genome-wide association studies (GWASs) comprising 2,039 pancreatic cancer cases and 32,592 controls, the largest sample size in the Japanese population. We identified 3 (13q12.2, 13q22.1, and 16p12.3) genome-wide significant loci (P<5.0×10 -8 ) and 4 suggestive loci (P<1.0×10 -6 ) for pancreatic cancer. Of these risk loci, 16p12.3 is novel; the lead SNP maps to rs78193826 (odds ratio (OR)=1.46, 9… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This hypothesis is supported by a previous genome‐wide association study (GWAS) in Japanese individuals, which identified three pancreatic cancer susceptibility loci that were not observed to be associated with risk in prior GWAS studies of individuals of European ancestry . A recent GWAS meta‐analysis of three Japanese studies further found a genetic risk marker in GP2 that is also distinct to this population . In addition, non‐O blood alleles, which are associated with pancreatic cancer, appear to be more prevalent in Japanese individuals compared to Europeans …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This hypothesis is supported by a previous genome‐wide association study (GWAS) in Japanese individuals, which identified three pancreatic cancer susceptibility loci that were not observed to be associated with risk in prior GWAS studies of individuals of European ancestry . A recent GWAS meta‐analysis of three Japanese studies further found a genetic risk marker in GP2 that is also distinct to this population . In addition, non‐O blood alleles, which are associated with pancreatic cancer, appear to be more prevalent in Japanese individuals compared to Europeans …”
Section: Discussionmentioning
confidence: 71%
“…[34][35][36] A recent GWAS meta-analysis of three Japanese studies further found a genetic risk marker in GP2 that is also distinct to this population. 37 In addition, non-O blood alleles, which are associated with pancreatic cancer, 38 appear to be more prevalent in Japanese individuals compared to Europeans. 39…”
Section: Discussionmentioning
confidence: 99%
“…These findings are particularly noteworthy as they unveil an Asian-specific GP2 gene variant that was previously overlooked in Western populations. Additionally, considering that GP2 variants are associated with a range of diseases and conditions beyond pancreatic cancer, including body mass index (BMI) (rs12597579) [116], type 1 [117] and 2 diabetes (rs117267808) [118], acute myeloid leukemia [119], and sleep quality [120], this study revealed the pleiotropic effects of GP2 variants, suggesting their potential roles in metabolic traits such as type 2 diabetes [63,118]. In fact, in a comprehensive GWAS involving Japanese subjects, the top 3 16p12.3 locus SNPs, including rs78193826, showed significant associations with type 2 diabetes, glycated hemoglobin (HbA1c), and blood glucose levels [121].…”
Section: The Role Of Gp2 In Other Diseases and Its Potential As A The...mentioning
confidence: 97%
“…However, whether these mutations are pathogenic has rarely been studied. It was not until 2020 that a groundbreaking study based on a meta-analysis of three genome-wide association study (GWAS) datasets comprising 2039 pancreatic cancer patients and 32,592 controls from Japan confirmed the relatively pivotal role of GP2 gene variants in pancreatic cancer [63]. This study analyzed a total of 7,914,378 SNPs across the whole genome and revealed three genome-wide significant loci associated with pancreatic cancer risk in this population: 13q12.2, 13q22.1, and the previously unreported 16p12.3 locus.…”
Section: The Role Of Gp2 In Other Diseases and Its Potential As A The...mentioning
confidence: 99%
See 1 more Smart Citation